DETERMINANTS OF DEMAND FOR A TOURIST PRODUCT. EXAMPLE OF THE LOCAL TOURIST MARKET (Research Bulletins of the Faculty of Economic Sciences, 2019)
The article has a theoretical and empirical character, its main goal was to determine the most important determinants shaping tourist demand. The study was based on determinants of a universal nature, occurring both on local and regional, national and global markets. The research problem was formulated in the form of a question about what are the main determinants of tourism demand? The hypothesis assuming the relationship between the tourist product and the determinants of its demand was verified. It was also assumed that the biggest impact on the product selection is the monthly income, age and nature of the trip. The Chi-square independence test and the Czuprow convergence test were used to verify hypotheses. Based on the results of statistical tests, a hierarchical system of determinants was established, defining their significance for the selection of a tourist product. The article uses available literature, and the main source of data used for empirical analysis was primary data collected through a diagnostic survey conducted on the local tourism market.
Keywords: determinants, demand, tourism product, dependencies, relationships.